2017
DOI: 10.1111/tri.12997
|View full text |Cite
|
Sign up to set email alerts
|

The attitude of Latin American immigrants in Florida (USA) towards deceased organ donation - a cross section cohort study

Abstract: The Latin American (LA) population resident in the USA is a growing subgroup of the population. To find out the structure of attitude towards organ donation in the LA population resident in Florida (USA). A sample was taken of LA residents in Florida, randomized and stratified by nationality, age and sex (n = 1524). Attitude was assessed using a validated questionnaire (PCID-DTO Rios) that was self-completed anonymously. The survey completion rate was 95% (n = 1450). Attitude was favourable in 33% of responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(21 citation statements)
references
References 27 publications
2
18
0
1
Order By: Relevance
“…First, it has been reported that Southeast Asians, including Japanese, are more reluctant to provide consent for organ donation than are white people [23,50]. Because the tradition of maintaining physical integrity of the body after death is prevalent, the majority of such subjects are less likely to register as an organ donor compared to those without such background [51][52][53]. This tradition is also maintained in Shinto, the most widespread religion in Japan [10,54].…”
Section: Discussionmentioning
confidence: 99%
“…First, it has been reported that Southeast Asians, including Japanese, are more reluctant to provide consent for organ donation than are white people [23,50]. Because the tradition of maintaining physical integrity of the body after death is prevalent, the majority of such subjects are less likely to register as an organ donor compared to those without such background [51][52][53]. This tradition is also maintained in Shinto, the most widespread religion in Japan [10,54].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that 30% of respondents say that either their religion has not pronounced about organ donation or they do not know what position it holds. This information is important in relation to being able to propose training campaigns for health personnel in this scope (4,(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Authors: Ríos A [1][2][3][4] , López-Navas A 1,5 , Gutiérrez PR 6 , Gómez FJ 7 , Iriarte J 8 , Herruzo R 9 , Blanco G 10 , Llorca FJ 11 , Asunsolo A 12 , Sánchez P 13 , Fernández A 14 , de Jesús MT 15 , Martínez Alarcón L 1,3 , Lana A 16 , Fuentes L 17 , Hernández JR 18 , Virseda J 19 , Yelamos J 21 , Bondía JA 13 , Hernández AM 21 , Ayala MA 1,[22][23][24] , Flores-Medina J 5 , Carrillo J 1,2 , Sánchez Á 1 , Ramírez P [1][2][3][4] , Parrilla P [2][3] .…”
Section: Title Page: Do Religious Factors Influence the Attitude Towaunclassified
“…Influence of bodily integrity, media, knowledge, and religion can determine a man's dedication toward organ donation and play a vast part in a man's eagerness to give their organs after death (Oliver, Woywodt, Ahmed, & Saif, ; Radecki & Jaccard, ). Knowing people's attitudes toward organ donation and the focal contructs behind the attitudes also help us to take more specific actions (Ríos et al, ; Ríos Zambudio, ).…”
Section: Introductionmentioning
confidence: 99%